High-thermal-conductivity aluminum oxide ceramic material and new energy battery cover plate
By using high-thermal conductivity alumina ceramic materials and using beryllium oxide to coat one-dimensional carbon materials and thermal toughening agents, the weight, sealing, corrosion resistance and collision strength problems of traditional battery boxes and covers are solved, and the heat dissipation performance of the materials is improved, achieving the excellent performance requirements of new energy battery covers.
Patent Information
- Application Number
- CN202411890513.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
AI Technical Summary
The traditional metal battery box and cover plate have a large weight, poor sealing, poor corrosion resistance, complex processing technology and low impact strength, which is not conducive to lightweight design of automobiles. At the same time, the thermal conductivity of alumina is low and cannot meet the heat dissipation needs of battery cover plates.
High thermal conductivity alumina ceramic material is used, which includes alumina, zirconium oxide, thermal toughening agent and beryllium oxide coated with one-dimensional carbon material. The network structure is formed by coating the one-dimensional carbon material through beryllium oxide, and thermal toughening agent is added to improve the thermal conductivity and toughness of the material.
The excellent flexural strength, fracture toughness and high thermal conductivity of the material are achieved, with flexural strength reaching 370MPa, thermal conductivity reaching 60.6W/(m·K), and fracture toughness reaching 8MPa·m1/2, meeting the needs of new energy battery covers.
Smart Images

Figure CN119707467A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of ceramic materials, and specifically relates to a high thermal conductivity alumina ceramic material and a new energy battery cover. Background Art
[0002] As the core component of new energy vehicles, the safety of power batteries directly affects the safety of the entire vehicle. The power battery system of pure electric vehicles is usually arranged under the floor of the vehicle body, and the operating environment is relatively harsh. The battery box and cover, as the carrier of the power battery, play a key role in the safe operation and protection of the battery pack. Its safety, reliability and durability are extremely important and determine the performance of the entire vehicle.
[0003] At present, traditional battery cases and covers are made of metal materials, such as steel or aluminum alloy. On the one hand, metal cases and covers are heavy, which will reduce the energy efficiency of the battery. On the other hand, they have poor sealing, which can easily cause the battery to be immersed in water and cause a short circuit. Thirdly, they have poor corrosion resistance. In addition, they also have defects such as complex processing technology and low impact strength, which is not conducive to achieving lightweight design of automobiles.
[0004] Alumina is a widely used material for small and medium power ceramic substrates. It has relatively high mechanical strength, abundant sources and low prices, but its thermal conductivity is low, about 20W / (m·K), which is far from meeting the heat dissipation requirements of battery cover plates. Summary of the invention
[0005] The purpose of this application is to provide a high thermal conductivity alumina ceramic material and a new energy battery cover to solve the technical problems in the prior art that traditional metal battery cases and covers are heavy, have poor sealing, poor corrosion resistance, complex processing technology and low impact strength, which are not conducive to lightweight design of automobiles, and alumina has low thermal conductivity and cannot meet the heat dissipation requirements of the battery cover.
[0006] In order to achieve the above-mentioned object, the first aspect of the present application provides a high thermal conductivity alumina ceramic material, comprising the following raw materials in parts by weight:
[0007] 80-85 parts of aluminum oxide; 10-15 parts of zirconium oxide; 2-5 parts of thermal conductive toughening agent; 5-10 parts of beryllium oxide-coated one-dimensional carbon material;
[0008] Wherein, the thermal conductive toughening agent includes silica gel particles and graphitized carbon.
[0009] In one or more embodiments, the particle size of beryllium oxide in the beryllium oxide-coated one-dimensional carbon material is 0.5 to 5 μm, and the particle size of aluminum oxide and zirconium oxide is 0.5 to 5 μm.
[0010] In one or more embodiments, the thermal conductive toughening agent comprises the following components in parts by weight:
[0011] 8-12 parts of graphitized carbon, 8-12 parts of Tween, 45-55 parts of aluminum oxide, 8-12 parts of zirconium oxide, 2-5 parts of silica gel particles, and 15-20 parts of high polymer;
[0012] The high polymer includes one or more combinations of high-density polyethylene, high-density polypropylene and high-density polyolefin elastomer.
[0013] In one or more embodiments, the beryllium oxide-coated one-dimensional carbon material is beryllium oxide-coated carbon fiber or beryllium oxide-coated carbon nanotube.
[0014] In one or more embodiments, the high thermal conductivity alumina ceramic material has a flexural strength of ≥370 MPa, a thermal conductivity of ≥60.6 W / (m·K), and a fracture toughness of ≥8 MPa·m 1 / 2 .
[0015] In order to achieve the above object, the second aspect of the present application provides a method for preparing the high thermal conductivity alumina ceramic material described in any one of the above embodiments, comprising:
[0016] Beryllium oxide is added to water, followed by one-dimensional carbon material and Tween-80, and stirred for 4 to 6 hours to obtain a first intermediate product;
[0017] The first intermediate product is aged and centrifuged, and the precipitate is washed, dried, calcined, and ultrafinely ground to 0.5 to 5 μm to obtain a beryllium oxide-coated one-dimensional carbon material;
[0018] Alumina and zirconium oxide are mixed and ball-milled, and then mixed evenly with the beryllium oxide-coated one-dimensional carbon material and the thermal conductive toughening agent, pre-sintered, and ultra-finely ground to 3 to 10 μm to obtain a second intermediate product;
[0019] The second intermediate product is ball-milled again, dried, granulated, and pressed into a rough blank;
[0020] The rough blank is sintered at high temperature to obtain a high thermal conductivity alumina ceramic material.
[0021] In one or more embodiments, the step of adding beryllium oxide to water, then adding a one-dimensional carbon material and Tween-80, and stirring for 4 to 6 hours to obtain the first intermediate product further comprises:
[0022] The one-dimensional carbon material is subjected to plasma surface roughening treatment.
[0023] In one or more embodiments, in the steps of aging and centrifuging the first intermediate product, washing, drying and calcining the precipitate, the calcination temperature is 950 to 1600° C. and the calcination time is 3 to 5 hours.
[0024] In one or more embodiments, in the step of mixing and ball-milling alumina and zirconium oxide, and then uniformly mixing and pre-firing with the beryllium oxide-coated one-dimensional carbon material and the thermal conductive toughening agent, the pre-firing is carried out under an inert atmosphere, the pre-firing temperature is 900 to 1000° C., and the pre-firing time is 1 to 2 hours;
[0025] In the step of sintering the rough blank at high temperature, the temperature of the high temperature sintering is 1350-1500° C., and the time of the high temperature sintering is 1-4 hours.
[0026] In order to achieve the above-mentioned purpose, the third aspect of the present application provides a new energy battery cover plate, which is prepared using the high thermal conductivity alumina ceramic material described in any of the above-mentioned embodiments.
[0027] Different from the prior art, the beneficial effects of this application are:
[0028] The high thermal conductivity alumina ceramic material of the present application forms a network structure by coating a one-dimensional carbon material with beryllium oxide, which provides the material with super strong mechanical properties; on the other hand, a thermal conductive toughening agent is added, and the thermal conductive toughening agent includes graphitized carbon, silica gel particles and high polymers, which significantly improves the toughness, strength and thermal conductivity of the material, and can meet the needs of new energy battery cover plates;
[0029] The preparation method of the present application can introduce an etching effect on the surface of the carbon material by performing a plasma surface roughening treatment on the one-dimensional carbon material, making the surface rougher, thereby increasing the contact area with beryllium oxide and improving the mechanical bonding force; in addition, after the surface roughening treatment, the interface performance between the carbon material and other materials can be improved, thereby enhancing the mechanical properties of the composite material; the improved interface performance also helps to improve the durability and stability of the composite material;
[0030] The material of the present application has excellent flexural strength, fracture toughness and thermal conductivity, among which the flexural strength reaches 370MPa, the thermal conductivity reaches 60.6W / (m·K), and the fracture toughness reaches 8MPa·m 1 / 2 , which can meet the needs of new energy battery covers. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1It is a schematic flow chart of an implementation method of a method for preparing a high thermal conductivity alumina ceramic material of the present application. DETAILED DESCRIPTION
[0033] In order to enable those skilled in the art to better understand the technical solutions in the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present application.
[0034] At present, due to the need for heat dissipation, new energy battery covers are generally made of metals with excellent heat dissipation performance. Metals have defects such as heavy weight, poor sealing, poor corrosion resistance, complex processing technology and low impact strength, which are not conducive to the lightweight design of automobiles and the improvement of energy efficiency.
[0035] In order to solve the above problems, the applicant has developed a high thermal conductivity alumina ceramic material, which has high mechanical strength and low cost on the one hand, and high thermal conductivity on the other hand, which can meet the needs of new energy battery cover plates.
[0036] Specifically, in one embodiment, the high thermal conductivity alumina ceramic material of the present application includes the following raw materials in parts by weight:
[0037] 80-85 parts of aluminum oxide; 10-15 parts of zirconium oxide; 2-5 parts of thermal conductive toughening agent; 5-10 parts of beryllium oxide-coated one-dimensional carbon material.
[0038] Among them, the thermal conductive toughening agent includes silica gel particles and graphitized carbon.
[0039] The high thermal conductivity alumina ceramic material based on the above components, on the one hand, can provide the material with super mechanical properties by coating the one-dimensional carbon material with beryllium oxide; on the other hand, the thermal conductivity and toughness of the material are significantly improved by the thermal conductive toughening agent, so that the material can have excellent strength, toughness and thermal conductivity.
[0040] In one embodiment, the beryllium oxide-coated one-dimensional carbon material may be specifically beryllium oxide-coated carbon fiber; in another embodiment, the beryllium oxide-coated one-dimensional carbon material may also be beryllium oxide-coated carbon nanotube.
[0041] One-dimensional carbon materials play the role of short fiber toughening. Due to the super strong mechanical properties of one-dimensional carbon materials, more energy is consumed when pulling out and breaking, which is beneficial to prevent the expansion of ceramic cracks. Beryllium oxide coating is used to improve the dispersion performance of one-dimensional carbon materials, so that they are evenly dispersed in the material to form a network.
[0042] In one embodiment, the thermally conductive toughening agent may include the following components in parts by weight:
[0043] 8-12 parts of graphitized carbon, 8-12 parts of Tween, 45-55 parts of aluminum oxide, 8-12 parts of zirconium oxide, 2-5 parts of silica gel particles, and 15-20 parts of high polymer.
[0044] The high polymer includes one or more combinations of high-density polyethylene, high-density polypropylene and high-density polyolefin elastomer. The above-mentioned thermal conductive toughening agent can be prepared by mixing and stirring the components, and its preparation method is not described here.
[0045] In order to optimize the thermal conductivity of the material, in one embodiment, the particle size of beryllium oxide in the beryllium oxide-coated one-dimensional carbon material can be 0.5-5 μm, and the particle size of aluminum oxide and zirconium oxide can be 0.5-5 μm. The overall thermal conductivity of the material is significantly improved by using raw materials with ultrafine particle sizes.
[0046] Based on the high thermal conductivity alumina ceramic material of the above-mentioned embodiments, the thermal conductive toughening agent includes graphitized carbon, silica gel particles and high polymer. Graphitized carbon can improve the thermal conductivity of the material, silica gel particles can improve the toughness of the material, and high polymer further improves the strength and toughness of the material, thereby significantly improving the toughness, strength and thermal conductivity of the material, which can meet the needs of new energy battery cover plates.
[0047] This application also provides a method for preparing the above-mentioned high thermal conductivity alumina ceramic material. Figure 1 , Figure 1 It is a schematic flow chart of an implementation method of a method for preparing a high thermal conductivity alumina ceramic material of the present application.
[0048] like Figure 1 As shown, the preparation method comprises:
[0049] S100, adding beryllium oxide into water, and then adding one-dimensional carbon material and Tween-80, stirring for 4 to 6 hours to obtain a first intermediate product.
[0050] S200, aging and centrifuging the first intermediate product, washing, drying, calcining, and ultrafinely grinding the precipitate to 0.5-5 μm to obtain a beryllium oxide-coated one-dimensional carbon material.
[0051] First, the beryllium oxide-coated one-dimensional carbon material can be prepared by a method of stirring and mixing followed by calcination, and after the calcination, ultrafine grinding is performed to ensure the particle size of the material.
[0052] In one embodiment, the calcination temperature may be 950-1600° C., and the calcination time may be 3-5 hours.
[0053] In one embodiment, in order to optimize the coating effect of beryllium oxide on the one-dimensional carbon material and improve the mechanical properties of the subsequent material, before S100, the following steps are further included:
[0054] S10, performing plasma surface roughening treatment on the one-dimensional carbon material.
[0055] Through surface roughening treatment, etching can be introduced on the surface of carbon fiber to make the surface rougher, thereby increasing the contact area with beryllium oxide and improving mechanical bonding strength; in addition, surface roughening treatment can improve the interface performance between carbon materials and other materials, thereby enhancing the mechanical properties of composite materials; improved interface performance also helps to improve the durability and stability of composite materials.
[0056] Furthermore, after the beryllium oxide-coated one-dimensional carbon material is prepared, the method further comprises:
[0057] S300, mixing alumina and zirconium oxide and ball milling, then uniformly mixing with beryllium oxide-coated one-dimensional carbon material and thermal conductive toughening agent, pre-sintering, and ultra-fine grinding to 3-10 μm to obtain a second intermediate product.
[0058] In one embodiment, the pre-calcination may be performed under an inert atmosphere, the pre-calcination temperature may be 900-1000° C., and the pre-calcination time may be 1-2 hours.
[0059] The inert gas may be conventional inert gases such as nitrogen and argon, which can achieve the effect of this embodiment.
[0060] S400, the second intermediate product is ball-milled again, dried, granulated, and pressed into a rough blank.
[0061] S500, sintering the rough blank at high temperature to obtain a high thermal conductivity alumina ceramic material.
[0062] In one embodiment, the high temperature sintering temperature may be 1350-1500° C., and the high temperature sintering time may be 1-4 hours.
[0063] Based on the preparation methods of the above-mentioned embodiments, a one-dimensional carbon material is subjected to plasma surface roughening treatment, and then mixed with beryllium oxide in water, stirred, centrifuged, and calcined to prepare a beryllium oxide-coated one-dimensional carbon material; the beryllium oxide-coated one-dimensional carbon material is then mixed with other raw materials for pre-sintering, pressing, and high-temperature sintering to prepare a ceramic material with excellent strength, toughness, and thermal conductivity, which can meet the needs of new energy battery cover plates, and at the same time, the raw materials are widely available and the cost is relatively low.
[0064] The effects of the technical solution of the present application are further elaborated in detail below in conjunction with specific embodiments.
[0065] Embodiment 1:
[0066] A high thermal conductivity alumina ceramic material, comprising the following raw materials in parts by weight: 82 parts of alumina; 13 parts of zirconium oxide; 5 parts of a thermal conductive toughening agent; and 8 parts of a beryllium oxide-coated one-dimensional carbon material.
[0067] Among them, the particle size range of beryllium oxide in the one-dimensional carbon material coated with alumina, zirconium oxide and beryllium oxide is 0.5-5 μm; the thermal conductive toughening agent includes the following components in parts by weight: 10 parts of graphitized carbon, 10 parts of Tween, 50 parts of alumina, 10 parts of zirconium oxide, 3 parts of silica gel particles, and 17 parts of high-density polyethylene.
[0068] The preparation method of the above-mentioned high thermal conductivity alumina ceramic material comprises:
[0069] Beryllium oxide was added to water, followed by one-dimensional carbon material and Tween-80, and stirred for 5 hours; then aged and centrifuged, the precipitate was washed, and dried at 80°C for 10 hours; then transferred to a muffle furnace and heated to 980°C at a rate of 10°C / min for calcination for 4 hours, and ultra-finely ground to 0.5-5μm to obtain a beryllium oxide-coated one-dimensional carbon material;
[0070] Alumina and zirconium oxide are mixed and ball-milled for 4 hours, then mixed evenly with beryllium oxide-coated one-dimensional carbon material and thermal conductive toughening agent, pre-calcined for 1 hour in a nitrogen atmosphere, and ultra-finely ground to 3-10 μm to obtain a second intermediate product;
[0071] The second intermediate product is ball-milled again, dried, granulated, and pressed at 50 MPa to obtain a rough blank;
[0072] The rough blank is sintered at 1480°C for 2 hours to obtain a high thermal conductivity alumina ceramic material.
[0073] Embodiment 2:
[0074] A high thermal conductivity alumina ceramic material, the preparation method is the same as that of Example 1, except that:
[0075] The high thermal conductivity alumina ceramic material of Example 2 comprises the following raw materials in parts by weight: 85 parts of alumina; 10 parts of zirconium oxide; 5 parts of thermal conductive toughening agent; 10 parts of beryllium oxide-coated one-dimensional carbon material;
[0076] Among them, the particle size range of beryllium oxide in the one-dimensional carbon material coated with aluminum oxide, zirconium oxide and beryllium oxide is 0.5-5 μm; the thermal conductive toughening agent includes the following components in parts by weight: 12 parts of graphitized carbon, 12 parts of Tween, 55 parts of aluminum oxide, 8 parts of zirconium oxide, 2 parts of silica gel particles, and 15 parts of high-density polypropylene.
[0077] Embodiment 3:
[0078] A high thermal conductivity alumina ceramic material, the preparation method is the same as that of Example 1, except that:
[0079] The high thermal conductivity alumina ceramic material of Example 3 comprises the following raw materials in parts by weight: 80 parts of alumina; 15 parts of zirconium oxide; 2 parts of thermal conductive toughening agent; 5 parts of beryllium oxide-coated one-dimensional carbon material;
[0080] Among them, the particle size range of beryllium oxide in the one-dimensional carbon material coated with aluminum oxide, zirconium oxide and beryllium oxide is 0.5-5 μm; the thermal conductive toughening agent includes the following components in parts by weight: 8 parts of graphitized carbon, 8 parts of Tween, 45 parts of aluminum oxide, 12 parts of zirconium oxide, 5 parts of silica gel particles, and 20 parts of high-density polyolefin elastomer.
[0081] Comparative Example 1:
[0082] A high thermal conductivity alumina ceramic material, which is basically the same as Example 1, except that:
[0083] The high thermal conductivity alumina ceramic material of Comparative Example 1 does not include beryllium oxide-coated one-dimensional carbon material.
[0084] Comparative Example 2:
[0085] A high thermal conductivity alumina ceramic material, which is basically the same as Example 1, except that:
[0086] The high thermal conductivity alumina ceramic material of Comparative Example 2 uses raw materials, and the particle size of alumina ranges from 10 to 30 μm.
[0087] Comparative Example 3:
[0088] A high thermal conductivity alumina ceramic material, which is basically the same as Example 1, except that:
[0089] No thermal conductive toughening agent is added to the high thermal conductive alumina ceramic material of Comparative Example 3.
[0090] Effect example:
[0091] The materials of Example 1 and Comparative Examples 1 to 3 were used as samples, and the flexural strength and fracture toughness of the samples were measured using an electronic universal testing machine. The room temperature thermal diffusion coefficient of the samples was tested using a laser thermal conductivity meter (Germany), and the thermal conductivity of the samples was calculated to obtain the data in the following table.
[0092]
[0093] As shown in the above table, the material of Example 1 has excellent flexural strength, fracture toughness and thermal conductivity, wherein the flexural strength reaches 370 MPa, the thermal conductivity reaches 60.6 W / (m·K), and the fracture toughness reaches 8 MPa·m 1 / 2 , which can meet the needs of new energy battery covers.
[0094] The material of Comparative Example 1 does not use beryllium oxide-coated one-dimensional carbon material and lacks a network structure constructed by dispersed beryllium oxide-coated one-dimensional carbon material. Therefore, the bending strength, fracture toughness and thermal conductivity are significantly lower than those of Example 1.
[0095] The material of Comparative Example 2 uses large-particle zirconium oxide as raw material. The particle size is too large, which is not conducive to improving the thermal conductivity and mechanical properties of the material.
[0096] The material of Comparative Example 3 does not use a thermally conductive toughening agent, resulting in the fracture toughness and thermal conductivity of the material being significantly lower than those of other embodiments and comparative examples.
[0097] It can be seen from the above experimental results that the thermal conductive toughening agent of the present application can significantly improve the thermal conductivity, toughness and strength of the material. The reason is that graphitized carbon has excellent thermal conductivity. At the same time, the addition of silica gel particles can improve the toughness of the material, and the high polymer also further improves the toughness and strength of the material.
[0098] It is obvious to those skilled in the art that the present application is not limited to the details of the exemplary embodiments described above, and that the present application can be implemented in other specific forms without departing from the spirit or essential features of the present application. Therefore, the embodiments should be regarded as exemplary and non-limiting in all respects, and the scope of the present application is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present application. Any reference numeral in a claim should not be regarded as limiting the claim to which it relates.
[0099] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A high thermal conductivity alumina ceramic material, characterized in that: It includes the following raw materials in parts by weight: 80-85 parts of aluminum oxide; 10-15 parts of zirconium oxide; 2-5 parts of thermal conductive toughening agent; 5-10 parts of beryllium oxide-coated one-dimensional carbon material; Wherein, the thermal conductive toughening agent includes silica gel particles and graphitized carbon.
2. The high thermal conductivity alumina ceramic material according to claim 1, characterized in that: The particle size of beryllium oxide in the beryllium oxide-coated one-dimensional carbon material is 0.5 to 5 μm, and the particle sizes of aluminum oxide and zirconium oxide are 0.5 to 5 μm.
3. The high thermal conductivity alumina ceramic material according to claim 1, characterized in that: The thermal conductive toughening agent comprises the following components in parts by weight: 8-12 parts of graphitized carbon, 8-12 parts of Tween, 45-55 parts of aluminum oxide, 8-12 parts of zirconium oxide, 2-5 parts of silica gel particles, and 15-20 parts of high polymer; The high polymer includes one or more combinations of high-density polyethylene, high-density polypropylene and high-density polyolefin elastomer.
4. The high thermal conductivity alumina ceramic material according to claim 1, characterized in that: The beryllium oxide coated one-dimensional carbon material is beryllium oxide coated carbon fiber or beryllium oxide coated carbon nanotube.
5. The high thermal conductivity alumina ceramic material according to claim 1, characterized in that: The high thermal conductivity alumina ceramic material has a bending strength of ≥370MPa, a thermal conductivity of ≥60.6W / (m·K), and a fracture toughness of ≥8MPa·m 1 / 2 .
6. A method for preparing the high thermal conductivity alumina ceramic material according to any one of claims 1 to 5, characterized in that: include: Beryllium oxide is added to water, followed by one-dimensional carbon material and Tween-80, and stirred for 4 to 6 hours to obtain a first intermediate product; The first intermediate product is aged and centrifuged, and the precipitate is washed, dried, calcined, and ultrafinely ground to 0.5 to 5 μm to obtain a beryllium oxide-coated one-dimensional carbon material; Alumina and zirconium oxide are mixed and ball-milled, and then mixed evenly with the beryllium oxide-coated one-dimensional carbon material and the thermal conductive toughening agent, pre-sintered, and ultra-finely ground to 3 to 10 μm to obtain a second intermediate product; The second intermediate product is ball-milled again, dried, granulated, and pressed into a rough blank; The rough blank is sintered at high temperature to obtain a high thermal conductivity alumina ceramic material.
7. The preparation method according to claim 6, characterized in that: The step of adding beryllium oxide into water, then adding one-dimensional carbon material and Tween-80, and stirring for 4 to 6 hours to obtain the first intermediate product also includes: The one-dimensional carbon material is subjected to plasma surface roughening treatment.
8. The preparation method according to claim 6, characterized in that: In the steps of aging and centrifuging the first intermediate product, washing, drying and calcining the precipitate, the calcination temperature is 950 to 1600° C. and the calcination time is 3 to 5 hours.
9. The preparation method according to claim 6, characterized in that: In the step of mixing and ball-milling alumina and zirconia, and then uniformly mixing and pre-firing with the beryllium oxide-coated one-dimensional carbon material and the thermal conductive toughening agent, the pre-firing is carried out in an inert atmosphere at a temperature of 900 to 1000° C. and a pre-firing time of 1 to 2 hours; In the step of sintering the rough blank at high temperature, the temperature of the high temperature sintering is 1350-1500° C., and the time of the high temperature sintering is 1-4 hours.
10. A new energy battery cover, characterized in that: It is prepared using the high thermal conductivity alumina ceramic material described in any one of claims 1 to 5.
Citation Information
Patent Citations
High-strength and high-heat conduction insulating material
CN102786721A
High-thermal-conductivity material and preparation method thereof
CN115073067A
High-thermal-conductivity aluminum oxide ceramic material and ceramic circuit substrate
CN116239367A
Sealing and sealing powder material for long-life spark plug and preparation method of sealing and sealing powder material
CN118851738A
Heat conductive high polymer body
JP1997321191A
Cited By
High-thermal-conductivity aluminum oxide ceramic and preparation process thereof
CN119462104A
High thermal conductivity aluminum oxide ceramic and preparation process thereof
CN119462104B